KONFLIK ANTARA KELOMPOK TANI DENGAN PENGURUS KUD PRIMA SEHATI (STUDI KASUS : PADA LOKASI DESA KENEGERIAN CENGAR KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI) - Iya Nevila Hawari; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in Kenegerian Cengar Village, Kuantan MudikSubdistrict, Kuantan Singingi Regency with the aim to obtain information aboutthe conflict between Farmer Group and KUD Prima Sehati. The several problemsin this research are (1) How are the forms of conflict between members of FarmerGroup and KUD Prima Sehati? (2) How is the process of resolving the conflictbetween the Farmer Group and the KUD Prima Sehati? The title of this study is": Conflicts Between Farmer Group and KUD Prima Sehati". The researchundertaken aims To find out how the forms and how the process of conflictresolution that occurs between the Farmer Group with KUD Prima Sehati inKenegerian Cengar Village, Kuantan Mudik Subdistrict, Kuantan SingingiRegency. In research, the subject of the study amounted to eight people. Thesubject are those who know how the conflict is going and involved in the conflictdirectly. The data were collected by interview, observation, and documentation.The interviews conducted were in-depth interviews. After doing this research, theforms of conflict that occurred in the village of Kenegerian Cengar KuantanMudik Sub-district Kuantan Singingi Regency are a demonstration, blocking ofroads and mass harvest, burning the field house KUD Prima Sehati, and there aredivisions within the community. The settlement efforts are done by mediating withboth parties and questioning how the management of KUD Prima Sehati for thenext and found the decision by vote caounting that administrators of KUD PrimaSehati must be replaced.Keywords: Conflict, Farmer Group, KUD Prima Sehati Management